Biological Activitivies Of Acanthophora Spicifera (VAHL) Borgesen From Pulau Gedung, Penang - Zakaria, Nurul Aili (2011)
A total of eight extract of Acanthophora spicifera extracted using two different methods using solvents of different polarity, were used throughout this study. These extracts were assayed to determine the antimicrobial activities, antioxidant activities, in-vitro cytotoxicity and total phenolic contents. Most of the extracts exhibited antibacterial activity against the tested bacteria. Meanwhile, no antifungal activity was observed on tested fungi. Among the extract, crude methanol extract demonstrated promising antibacterial activity against Gram-negative Pseudomonas aeruginosa ATCC 27853 with inhibition zone of 11.0 mm, MIC values of 250 μg mL-1 and MBC value of 500 μg mL-1. A. spicifera also exhibited antioxidant properties.